Evaluation of quality parameters of chicken eggs stored at different temperatures - Sema SANDIKÇI ALTUNATMAZ; Filiz AKSU; Deniz AKTARAN BALA; İbrahim AKYAZI; Cansu ÇELİK (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2019)
This study was carried out to evaluate the effect of temperature and time on the internal and external quality of chicken eggs stored at room and fridge temperature for 28 days. A total of 176 eggs of Lohmann Brown (LSL) laying hens were used for the study. The eggs from the same batch were stored at fridge (5°C) and room temperature (25°C), internal and external quality parameters and microbiological analyzes of eggs were evaluated on days 0, 1, 8, 18, 21 and 28. No coliform bacteria, E. coli and Salmonella spp. were detected. At the end of the evaluation, the eggs stored at room temperature were found to have been negatively affected in terms of albumen index and Haugh unit parameters from day 8 onwards. When a comparison was made between the eggs kept in the room and the fridge temperature, significant differences were found in terms of albumen index, Haugh unit, egg yolk index and egg yolk height parameters (P<0.05). As a result, it is predicted that the storage temperature and duration play an important role in preserving the freshness of the eggs and the eggs should be kept under the cold chain, especially from day 8 onwards after the egg laying date.